Cell Therapy in Veterinary Medicine as a Proof-of-Concept for Human Therapies: Perspectives From the North American Veterinary Regenerative Medicine Association - Arzi, Boaz; Webb, Tracy L.; Koch, Thomas G.; Volk, Susan W.; Betts, Dean H.; Watts, Ashlee; Goodrich, Laurie; Kallos, Michael S.; Kol, Amir (Frontiers in Veterinary Science, 2021)
In the past decade, the potential to translate scientific discoveries in the area of regenerative therapeutics in veterinary species to novel, effective human therapies has gained interest from the scientific and public domains. Translational research using a One Health approach provides a fundamental link between basic biomedical research and medical clinical practice, with the goal of developing strategies for curing or preventing disease and ameliorating pain and suffering in companion animals and humans alike. Veterinary clinical trials in client-owned companion animals affected with naturally occurring, spontaneous disease can inform human clinical trials and significantly improve their outcomes. Innovative cell therapies are an area of rapid development that can benefit from non-traditional and clinically relevant animal models of disease. This manuscript outlines cell types and therapeutic applications that are currently being investigated in companion animals that are affected by naturally occurring diseases. We further discuss how such investigations impact translational efforts into the human medical field, including a critical evaluation of their benefits and shortcomings. Here, leaders in the field of veterinary regenerative medicine argue that experience gained through the use of cell therapies in companion animals with naturally occurring diseases represent a unique and under-utilized resource that could serve as a critical bridge between laboratory/preclinical models and successful human clinical trials through a One-Health approach.